Improving public services by sharing the right information. Issue 5 (4th July 2019) - Curtis, Stephen; Edwards, John
ABSTRACT: This article looks at the role that information sharing plays in supporting new models of public service delivery. It sets out the barriers to information sharing, attempts to overcome them and considers some of the factors involved in shaping a new direction for information sharing, such as changing public expectations and the rapidly changing regulatory environment. IMPACT: Information sharing is often cited as being a barrier to the transformation of public services, for example child protection, domestic abuse and serious crime. This article explains what needs to be done to deal with these issues.